Corporate Governance Practices, Operating Environment and Financial Sustainability of Saccos in Greater Mbarara District - Atukunda, Gershom; Musiita, Benjamin; Atwiine, Johnson; Atwine, Aquilionus; Olyanga, Anthony Moni (Journal of Economics and Behavioral Studies, 2024)
This study investigated the link between corporate governance practices, the operating environment, and the financial sustainability of Savings and Credit Cooperatives (SACCOs) in the Greater Mbarara region. It aimed to understand how each factor, and their combined effect, influence SACCO’s financial health. The study employed a cross-sectional design and analyzed data from 164 SACCOs (sample size determined using Krejicie and Morgan table (1970). Statistical analysis revealed that both corporate governance practices and the operating environment have a positive and significant relationship with SACCO’s financial sustainability. Additionally, their combined effect was also found to be positive and significant. The results suggest that 42.6% of the variation in financial sustainability can be explained by these two factors, leaving 57.4% to be influenced by other, unexplored aspects. To further improve SACCO’s financial health in the region, the study recommends fostering communication with decision-makers, collaborating with governance and environmental experts, and implementing continuous monitoring of governance initiatives and environmental adaptations.